2021
DOI: 10.5114/aic.2021.111926
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology, management, and survival rate of out-of-hospital cardiac arrest in Upper Silesia, Poland: an Utstein-style report

Abstract: Introduction: Despite the growing number of studies on the epidemiology of out-of-hospital cardiac arrest (OHCA) in Poland, this issue has not been sufficiently studied. Notably, there has been a lack of uniform Utstein-style data reporting.Aim: To evaluate the epidemiology of OHCA, patient characteristics, the laypeople and emergency medical service (EMS) response to cardiac arrest, and outcomes of OHCA patients, based on a prospective registry encompassing a population of 2.7 million Poles.Material and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 29 publications
0
4
0
Order By: Relevance
“…PCN/CBN/0022/KB/159/21), given the observational nature of the study. The study design of SIL-OHCA and other details on the registry have been presented previously [15][16][17].…”
Section: Sil-ohca Registrymentioning
confidence: 99%
“…PCN/CBN/0022/KB/159/21), given the observational nature of the study. The study design of SIL-OHCA and other details on the registry have been presented previously [15][16][17].…”
Section: Sil-ohca Registrymentioning
confidence: 99%
“…Machine learning is a branch of artificial intelligence that has proven increasingly useful in medicine [1][2][3]. The annual incidence of out-of-hospital cardiac arrests (OHCA) is 34.7-156.0/100000 people in the word [4]. OHCA result in high mortality and poor prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, fear of contamination of SARS-CoV-2 might result in more reserved attitudes toward resuscitation practice and a lower rate of successful cardiopulmonary resuscitation (CPR) [7][8][9][10]. The population at risk remained constant; however, recent studies reported a growing incidence of OHCA and a decreased number of STEMI with detrimental outcomes during the pandemic era [7][8][9][10][11]. Limited access to healthcare, more reluctant health-seeking behaviors, and bystander readiness to render life-saving interventions might additionally contribute to the suggested change in the risk of OHCA in STEMI [4][5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…The population at risk remained constant; however, recent studies reported a growing incidence of OHCA and a decreased number of STEMI with detrimental outcomes during the pandemic era [7][8][9][10][11]. Limited access to healthcare, more reluctant health-seeking behaviors, and bystander readiness to render life-saving interventions might additionally contribute to the suggested change in the risk of OHCA in STEMI [4][5][6][7][8][9][10][11]. Despite the remarkable growth of evidence, there is a lack of data on clinical outcomes in STEMI complicated by OHCA during the COVID-19 pandemic compared to the pre-pandemic era.…”
Section: Introductionmentioning
confidence: 99%